Isabella Bonarelli della Rovere: A Story of Disputed Identity - Lanza, Stefano M. (Senoji Lietuvos literatūra, 2021)
Unlike Guidubaldo and Prospero Bonarelli della Rovere, who rose to literary fame, Countess Isabella (d. 1602), wife of the eclectic noble of the Grand Duchy of Lithuania Teodor Lacki, is a figure of little importance in Italian historiography. According to the few sources mentioning her it is clear that she was the sister of the noble Count Pietro Bonarelli, from Italy’s Marche region, and with him she fled hastily the city of Urbino when he fell into disgrace of the new prince. The family moved eventually to Novellara and the scholar of local antiquities Giuseppe Campori (1821-1887) reports that a daughter of the count, whose name he is not certain of (he gives only its initial, ‘N.’), was maritata a Teodoro Laczki gentiluomo polacco (“married to Teodor Lacki, Polish gentleman”). These reports are not in contrast with each other, but are nonetheless inconsistent with Lithuanian sources, primarily the Funeral oration (and the collection of poems that accompanies it), written in honor of Isabella by Johannes Kimbar. Whilst Italian scholars had the advantage of direct access to original documents in loco, on the other hand, one cannot doubt the information that can be deduced from Isabella’s eulogy. Not only for chronological reasons, but especially because Kimbar was at the service of Lacki as well as personally acquainted with his circle, he deserves more credit, conventional formulas of the apologetic repertoire put aside. It does not seem possible that this literate could have reported inaccurate information in his erudite works, later given to the press, in which he recalls moments in the life of the Italian noblewoman, especially since his occasional speech is expressly dedicated to people who knew the deceased even better than the author did. Therefore, the question whether Isabella was the sister of Count Pietro Bonarelli, rather than his daughter, looks pointless from a logical point of view. Still the discrepancies between the mentioned sources require an explanation. A comparison of Italian documents of various types referring to the members of the Bonarelli family from those two generations, even texts which date to their same period, highlights disagreements on dates, names, places and even significant life events. For these reasons, while some hypotheses remain yet to be proved, the reconstruction proposed here should not be far from the truth.